2015
DOI: 10.4238/2015.june.18.3
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 is a tumor suppressor in cervical cancer

Abstract: ABSTRACT. Forkhead box protein O1 (FOXO1) is an important transcriptional regulator of cell proliferation, and is considered essential for tumor growth and progression. However, the function of FOXO1 in human cervical cancer remains unclear. In this study, we investigated the role of FOXO1 in cervical cancer. Our results showed that FOXO1 expression was lower in cervical cancer than in cervical intraepithelial neoplasia and normal cervix by immunohistochemical analysis (P < 0.05). The level of FOXO1 in high-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 28 publications
6
49
0
Order By: Relevance
“…We first examined the expression level of the transcriptional factor, FOXO1, in four different cervical cancer cell lines (HeLa, Caski, SiHa, and C-33A). Our results confirmed that two well-characterized cell lines, C-33A and Siha expressed FOXO1 at the highest and lowest levels, respectively (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…We first examined the expression level of the transcriptional factor, FOXO1, in four different cervical cancer cell lines (HeLa, Caski, SiHa, and C-33A). Our results confirmed that two well-characterized cell lines, C-33A and Siha expressed FOXO1 at the highest and lowest levels, respectively (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Research shows the vital involvement of FOX family in cancer onset and progression, and miRNAs play a crucial regulatory role in tumors via the modulation of these FOX proteins (Zhang et al, 2015;Wang et al, 2016). Foxf2 gene belongs to the forkhead/winged helix transcription factor family and has been implicated as an oncogene that modulates metastasis of various tumors (Nilsson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When FOXO1 is overexpressed, cell proliferation and growth is inhibited by upregulating caspase-3 and caspase-9 and inducing G2/M arrest and (Yang et al 2015). BCL2L1 and BCL2L2, BCL2 family, are pro-oncogene and repress intrinsic pathwaymediated cell death (Denoyelle et al 2014;Zhang et al 2015). Other genes, PTEN, BBC3, and MDM2, also rescue cell death and induce proliferation (Fortunato et al 2014;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%